METHODICAL APPROACH FOR INCREASING OF OTS FUNCTIONING EFFICIENCY - Самков, О.; Крамаренко, Т.; Калакура, Р.; Кобулей, А. (Science-based technologies, 2011)
Designed methodical approach for increasing of OTS functioning efficiency on the basis of selection of specialists of control and executive link with socionic features which minimize management cycle time in the automated control a production systems. Application offered methodical approach allows to make practical recommendations for services of management a personnel.